Labour mobility in the enlarged European Union: International migration from the EU8 countries - Agnieszka Fihel; Paweł Kaczmarczyk; Marek Okólski (University of Warsaw, Centre of Migration Research (CMR), 2006)
The present paper consists of an extensive description of recent migration in the 8 new European Union member countries which accessed the EU on May 1st, 2004. Since 1989 all of these countries experience an unique shift from socialist to market economy. The paper attempts to capture an interplay or correlation of pre- and post-enlargement developments with the phenomena of political and socio-economic transition on migration from and into this region.
Keywords: 330; Internationale Migration; Arbeitsmigranten; Migrationsforschung; EU-Mitgliedschaft; Prognose; EU-Mitgliedschaft